Divine doppelgängers : YHWH's ancient look-alikes - Cornell, Collin, 1988- (Eisenbrauns, 2020)
"A collection of essays by scholars of the Hebrew Bible providing recommendations for how Jews and Christians can think theologically about the challenge of similarities between YHWH and other ancient gods"--